APLIKASI BROADCASTER INFORMASI LOWONGAN KERJA BERBASIS SMS GATEWAY MENGGUNAKAN ALGORITMA FIRST INDEXING SEARCH - Hans Barrang; Mika Tandililing (Nusantara Hasana Journal, 2023)
Information technology in the current era of globalization is developing very rapidly. These technological advances have made the use of computers as an information system. The phenomenon found by the panelists is the obstacle faced by the Manpower Office in overcoming the increasing number of unemployed, namely information on the spread of job vacancies that are not managed optimally, so that every community is very small in terms of getting job opportunities. SMS Broadcast is a method of sending SMS to multiple numbers from one source or server with the same message content. Another term for bulk SMS is bulk SMS, Web2SMS, or SMS via the internet. The First Indexing Search method is included in the category of informed search algorithms (heuristic search), where the working principle is to make the best decision when a problem occurs which is expected to be the best solution. The use of the SMS Gateway feature on the system is carried out automatically when a company declares that it has received files sent by job seekers. It was concluded that the system that has been built can assist job seekers in obtaining information about job vacancies and this application can assist companies in finding professional workers mediated by the Makassar City Manpower Office.